PENGOPTIMALAN MANAJEMEN PENGENDALIAN PADA PT. MULIA SAFETY SERVICE - Djong, Alexander Mario Retto; Situmorang, Dokman Marulitua; Santoso, Ferry (Mount Hope Management International Journal, 2023)
This research has two main objectives. First, to find out the application of the company's purchasing accounting system. Second, to evaluate whether the internal control system in the company's purchasing accounting system is running optimally. This research is a qualitative descriptive study. The research results show that the internal control system over the purchasing accounting system at PT. Mulia Safety Service Surabaya is still not comprehensive, this is due to the dual function of the purchasing department (purchasing function and receiving function) and the lack of distribution of documents (goods receipt forms) which should also be received by the accounting department. Therefore, several improvements are needed. Firstly, by creating a separate receiving section as a receiving function or you can also give this authority to the inventory section, and secondly, the receiving function also creates a document (goods receipt form) so that not only the purchasing and inventory departments receive it but also the accounting department. This improvement is expected to optimize the purchasing accounting system at PT. Mulia Safety Service Surabaya.